PERANAN KOMPENSASI KARYAWAN DALAM PENINGKATAN MOTIVASI KERJA (STUDI KASUS DI PT. KUSUMAHADI SANTOSA) - Ningrum, Dwi Puspita; Santoso Th, Djoko; Widodo, Jumiyanto (Jurnal Informasi dan Komunikasi Administrasi Perkantoran, 2012)
Abstract: The aims of this research are to investigate the compensation system applied by PT. Kusumahadi Santosa weaving department on production division, and also to investigate the role of compensation on improving work motivation. This research was descriptive study used qualitative approach. The kind of research used was case study with one-pile strategy. The sources of the data were got from the informants, places and events, and also documents and archives. The researcher used purposive sampling and snowball sampling technique. The techniques of collecting data were interview, observation and documentation. The validity of the data was trianggulation of sources and method. The technique of analyzing the data was interactive analysis where the data reduction, data presentation and the drawing of the conclusion were related one each other. The result shows that the compensation system applied by PT. Kusumahadi Santosa is good. Whereas, the implementation of this system is included the purpose of compensation, kinds of compensation, compensation methods, basic principle of compensation-given, and the factors influence the compensation-given. Beside, The role of compensation system applied by PT. Kusumahadi Santosa had been well and proper. It supports of employee?s motivation improvement.   Key words: role, employee compensation, work motivation